2020
DOI: 10.3389/fbioe.2020.580135
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Electrospun Nanofibers and Fiber Alignment Enhance Neural Stem Cell Proliferation and Neuronal Differentiation

Abstract: Neural stem cells (NSCs) have the potential to generate the cells of the nervous system and, when cultured on nanofiber scaffolds, constitute a promising approach for neural tissue engineering. In this work, the impact of combining nanofiber alignment with functionalization of the electrospun poly-ε-caprolactone (PCL) nanofibers with biological adhesion motifs on the culture of an NSC line (CGR8-NS) is evaluated. A five-rank scale for fiber density was introduced, and a 4.5 level, corresponding to 70-80% fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…Furthermore, oriented nanofibers promote the growth of nascent axons, which may be involved in glutamate transport [224]. It has also been reported that oriented nanofibers can promote the recruitment and migration of endogenous neural stem cells and guide them and exogenous neural stem cells to differentiate into neurons, expressing higher levels of neuron-related proteins [225][226][227]. Nanoparticles are widely used in drug delivery systems due to their unique advantages, which can successfully reach and stay at the injury site for a long time, and achieve the purpose of promoting injury repair by continuously releasing growth factors, drugs, etc.…”
Section: Types Of Functional Biomaterialsmentioning
confidence: 99%
“…Furthermore, oriented nanofibers promote the growth of nascent axons, which may be involved in glutamate transport [224]. It has also been reported that oriented nanofibers can promote the recruitment and migration of endogenous neural stem cells and guide them and exogenous neural stem cells to differentiate into neurons, expressing higher levels of neuron-related proteins [225][226][227]. Nanoparticles are widely used in drug delivery systems due to their unique advantages, which can successfully reach and stay at the injury site for a long time, and achieve the purpose of promoting injury repair by continuously releasing growth factors, drugs, etc.…”
Section: Types Of Functional Biomaterialsmentioning
confidence: 99%
“…Additionally, membranes with small diameter fibers (about 250–300 nm) were a stronger support for dermal fibroblast proliferation than membranes composed of fibers with a diameter of about 1 μm [ 30 ]. It has been reported that biological nanofiber membranes could also induce and enhance stem cell differentiation compared to microfibers and play an important role in promoting regeneration [ [31] , [32] , [33] ]. Another study has revealed that the fiber diameter of membranes could affect the immune response of macrophages, especially in the early stage of inflammation, since nanofiber membranes minimize the inflammatory response relative to microfiber membranes [ 34 ] and manipulate tissue regenerative immune reactions [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laminin is one of the most important components of the basal membrane in the brain, while IKVAV and YIGSR belong to the α1 and β1 chains of laminin, respectively. Neurons cultured on PCL fibers functionalized with laminin showed better activity, higher number of neurons, and more uniform orientation of dendrites than neurons cultured on PCL fibers modified with RGD (Amores de Sousa et al, 2020). As some cytokines regulate neuronal growth, they can be immobilized with scaffold by biotin-streptomycin bonding, which can promote neuron growth even better than soluble cytokines (Kunze et al, 2011).…”
Section: Scaffold-based Culture Of Primary Neuronsmentioning
confidence: 99%
“…[(C), i] Schematic illustration of electrospinning. [(C), ii] Scanning electron microscopy of scaffold formed by aligned and random electrospun fibers ( Amores de Sousa et al, 2020 ).…”
Section: Scaffold-based Modelmentioning
confidence: 99%